Demand Interrelations for Selected Agricultural Products - Clawson, Marion (Quarterly Journal of Economics, 1943)
Interrelations of demand for meat: general characteristics of demand for meat, 265; interrelations of beef, pork, lamb, veal, and chicken 1899 to 1939, including shifts in interrelations, 269.— Interrelations of demand for fruit: apples and citrus fruits, 284; peaches in different producing areas, 290.— Interrelations of demand for grain: general characteristics of production and demand for corn, oats and barley, 292; interrelations 1866 to 1939, including shifts in relations, 293.— Significance of results obtained, 299.